Kesan personaliti terhadap keenganan latihan dikalangan kakitangan Jabatan Kastam Diraja Malaysia - Muhamad Kamil, Muhammad Zain (2019)
This research discussed the effect of personality on resistance to train among the staff at the Royal Customs of Malaysia, Port Klang. It was conducted to achieve five objectives: to determine whether (a) openness to experience personality affects resistance to train, (b) conscientiousness personality affects resistance to train, (c) extra version personality affects resistance to train, (d) agreeableness personality affects resistance to train, and (e) neuroticism personality affects resistance to train. This study involved the distribution of questionnaires among st 118 staff from Grade W19 to W44 who were selected randomly by using the proportionate stratified sampling frame. The researcher employed the International Personality Item Pool (IPIP) constructed by Bamber and Castka (2006) and resistance to train measurement developed by Oreg (2003). The result of factor analysis revealed that personality among the respondents involved in this study include agreeableness and neuroticism, while emotional reaction and short-term cognitive are the dimensions representing resistance to train. To examine the effect of personality on resistance to train, the researcher executed multiple regression analysis. The result showed that neuroticism personality significantly affects resistance to train. In other words, employees who are not emotionally stable will show their resistance to train. The researcher suggests that the Training Unit of the Royal Customs of Malaysia as well as the Royal Customs Academy (AKMAL) must do training needs analysis encompassed with organizational task, and individual analyses for each staff to maintain appropriateness of training and maintaining good facilities in the academy. The implications of the findings, future research and practice, and the limitations of the present study are also discussed.